Diatomite-based ceramic biocoating for magnesium implants; Ceramics International; Vol. 48, iss. 19 - Kashin A. D. Aleksandr Daniilovich; Sedelnikova M. B. Mariya Borisovna; Chebodaeva V. V. Valentina Vadimovna; Uvarkin P. V. Pavel Viktorovich; Luginin N. A. Nikita Andreevich; Dvilis E. S. Edgar Sergeevich; Kazmina O. V. Olga Viktorovna; Sharkeev Yu. P. Yury Petrovich; Khlusov I. A. Igor Albertovich; Miller A. A. Andrey Aleksandrovich; Bakina O. V. Olga Vladimirovna (2022, 2022)
Title screen